Visual Rhyme Judgment in Adults With Mild-to-Severe Hearing Loss - Rudner, Mary; Danielsson, Henrik; Lyxell, Björn; Lunner, Thomas; Rönnberg, Jerker (Frontiers in Psychology, 2019)
Adults with poorer peripheral hearing have slower phonological processing speed measured using visual rhyme tasks, and it has been suggested that this is due to fading of phonological representations stored in long-term memory. Representations of both vowels and consonants are likely to be important for determining whether or not two printed words rhyme. However, it is not known whether the relation between phonological processing speed and hearing loss is specific to the lower frequency ranges which characterize vowels or higher frequency ranges that characterize consonants. We tested the visual rhyme ability of 212 adults with hearing loss. As in previous studies, we found that rhyme judgements were slower and less accurate when there was a mismatch between phonological and orthographic information. A substantial portion of the variance in the speed of making correct rhyme judgment decisions was explained by lexical access speed. Reading span, a measure of working memory, explained further variance in match but not mismatch conditions, but no additional variance was explained by auditory variables. This pattern of findings suggests possible reliance on a lexico-semantic word-matching strategy for solving the rhyme judgment task. Future work should investigate the relation between adoption of a lexico-semantic strategy during phonological processing tasks and hearing aid outcome.